Nootkatone Alleviates Type 2 Diabetes in db/db Mice Through AMPK Activation and ERK Inhibition: An Integrated In Vitro and In Vivo Study - Yingjie Li; Linlin Zheng; Mimi Chen; Ruodi Li; Yansu Yu; Lu Qiao; Jialu Liu; Xiaopo Zhang; Yong Zhang; Yuxin Zhang; Wei Zheng (Molecules)
Type 2 diabetes mellitus (T2DM) is a common chronic metabolic disorder that imposes a substantial healthcare burden globally. Recent advances highlight the potential of natural products in ameliorating T2DM. In this study, we investigated the therapeutic efficacy of nootkatone (Nok), a natural sesquiterpene ketone, in T2DM and elucidated its underlying mechanisms. In vivo experiments demonstrated that Nok administration markedly improved dysregulated glucose metabolism and ameliorated serum biochemical abnormalities in db/db mice. Leveraging a network pharmacology-based approach, we identified putative molecular targets of Nok. Subsequent in vitro analyses revealed that Nok significantly enhanced glucose consumption in cultured cells. Mechanistically, Nok robustly activated AMP-activated protein kinase (AMPK) while suppressing mitogen-activated protein kinase (MAPK) signaling. Western blot validation further indicated that Nok downregulated the phosphorylation of MAPK1/3 (ERK2/1), attenuating MAPK pathway activation and thereby alleviating metabolic dysfunction-associated fatty liver disease (MAFLD) progression in the diabetic model. Collectively, our findings suggest that Nok exerts anti-diabetic effects via dual modulation of AMPK activation and MAPK inhibition, effectively restoring metabolic homeostasis and mitigating inflammation in T2DM. This study positions Nok as a promising natural compound for therapeutic intervention in T2DM and associated metabolic disorders.